The strain and transition metal doping effects on monolayer Cr2O3 for hydrogen evolution reaction: The first principle calculations. (30th October 2022) - Zhao, Ziwei; Liu, Chaoming; Tsai, Hsu-Sheng; Zhou, Jiaming; Zhang, Yanqing; Wang, Tianqi; Ma, Guoliang; Qi, Chunhua; Huo, Mingxue
Abstract: Chromic oxide (Cr2 O3 ) monolayer is a promising alternative hydrogen evolution reaction (HER) catalyst compared with expensive platinum (Pt) due to its advantages such as low cost, large specific surface area, high reserves, and designability. In this study, the two practical strategies, strain engineering and transition metal (TM) doping (Mn, Fe, Zn, etc.), are proposed to activate the catalytic sites of Cr2 O3 monolayer for the HER. The density functional theory (DFT) calculations demonstrate that the strained Cr2 O3 monolayer can stimulate the HER activity with the Gibbs free energy of hydrogen adsorption (ΔGH∗ ) close to 0.09eV, which can be considered as a performable strategy to tune the HER catalytic behavior of Cr2 O3 monolayer. For the TM doping, it also plays a role in the performance adjustment. These results provide a guideline to optimize the HER performance of Cr2 O3 monolayer. Graphical abstract: Image 1 Highlights: The HER catalytic behavior of monolayer Cr2 O3 is first theoretically predicted. The HER catalytic behavior of monolayer Cr2 O3 could be modulated by the strain. The TM-doped monolayer Cr2 O3 plays a certain role for the HER catalysis.